IDEOLOGI MEGALOMANIA TERHADAP SIMBOL “S” DALAM FILM SUPERMAN SEBAGAI BENTUK PROPAGANDA INTERNASIONAL AMERIKA SERIKAT - Reva Rinanda Siregar; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This Research describes that a film is able to actualize symbolize that canbecome an identity of state, community or individual. One of HollywoodMovies that is able to be a signifier from the strength of United Statesnamely the movie of Superman. Symbol “S” at the costume of Supermanbecomes signifier from the superpower of United States. “S” meansambiguity in the meaning of superpower and it has been stuck on theglobal society‟s mindset that United States is the only most super in thewhole wide world. US expands its hidden ideology through diplomacyespecially by culture expanding.This research uses analitif-descriptivemethod. The datas were obtained from internet, journals, and books. Then,they were collected, summarized and analyzed based on the socialresearch method. To analyze it, the writer uses postmodernismeperspective to explore the constructed mindset.This research explores the constructed mindset of Symbol “S” ofSuperman Movie where United States is always considered as supercountry through its Megalomania ideology that is hidden in every untoldicon. Through this movie, this research exactly wants to open thediscourse in order not to trap in the construction of mass media.Keywords: Cultural Diplomacy, Megalomania, Post-Modernism,Superman.